Adsorbate-induced roughening of Si(100) by interactions at steps - Butera, R. E. (2010)
Through a detailed study of Cl adsorption on Si(100) using scanning-tunneling microscopy, we identified sites at steps where adsorption leads to roughening and the formation of extended pits and regrowth structures. Using the equilibrium occupation probabilities obtained from experiment, we were able to identify first-nearest-neighbor interactions that destabilized the surface and, when included in Monte Carlo simulations, reproduced the observed pit and regrowth structures. These findings force a reevaluation of currently proposed mechanisms for roughening.